Failure properties of cubic granite, marble, and sandstone specimens under true triaxial stress. (June 2020) - Du, Kun; Yang, Chengzhi; Su, Rui; Tao, Ming; Wang, Shaofeng
Abstract: Cubic specimens of granite, marble, and sandstone, with side lengths of 50 mm, were prepared in the laboratory. True triaxial compression tests were conducted on each rock type with minor principal stress ( σ 3 ) magnitudes of 10, 20, 30, 50, and 100 MPa and the intermediate principal stress ( σ 2 ) varying from σ 2  =  σ 3 to σ 2  =  σ 1 (where σ 1 represents the major principal stress). The experimental results demonstrated that the failure strength, fracture dip angle, non-linear behavior and failure mode of these rocks under true triaxial conditions were affected by both σ 2 and σ 3, as well as by the rock lithology. When σ 3 was kept constant and σ 2 increased, failure strength showed an initial increase followed by a decrease, whereas the fracture dip angle increased monotonically. The non-linear behavior before the peak strength point of granite became more apparent by the increase of σ 3, whereas σ 2 had an opposite effect on the non-linear behavior of granite under high σ 3 (e.g. 100 MPa). The non-linear behavior before the peak strength point was always found in marble and sandstone for all of the stress state conditions. Analyses of fracture dip angle and failure mode showed that when σ 3  = 10, 20, and 30 MPa and σ 2 / σ 3  ≥ 5, 7.5, and 10, respectively, the failure mode of granite changed from shear to slabbing, whereas marble and sandstone always fractured in the shear direction. This study confirms that rocks may experience slabbing failure under true triaxial stress, and slabbing failure mode is likely to be induced in high-strength and brittle rocks under low σ 3 with the stress ratio of σ 2 / σ 3 exceeding a particular threshold value.